THE EFFECT OF DRILLING TECHNIQUE IN VOCABULARY MASTERY OF EIGHTH GRADE STUDENTS AT SMPS MARISI MEDAN - Veni Juwita; Christina Natalina Saragi; Fenty Debora Napitupulu (Prodi Pendidikan Bahasa dan Sastra Indonesia, Universitas Balikpapan, 2025)
This study aimed to examine the effect of the drilling technique on the vocabulary mastery of eighth-grade students at SMP Marisi. It employed a quantitative experimental design, involving an experimental class (VIII-1) that received vocabulary instruction using the drilling technique and a control class (VIII-2) that was taught using conventional methods. Data were collected through pre-tests and post-tests and were then analyzed using statistical methods to assess the effectiveness of the drilling technique in enhancing students' vocabulary acquisition. The findings revealed a significant difference in vocabulary mastery between students taught using the drilling technique and those who were not. Statistical analysis indicated that the experimental group's average pre-test score was 47.26, which increased to 65 in the post-test, reflecting an improvement of 17.73 points. In contrast, the control group's average score increased from 48 to 59.5, with a smaller gain of 11.5 points. The t-test analysis (t-count = 2.58, t-table = 2.021) confirmed that this difference was statistically significant (p < 0.05), leading to the acceptance of the alternative hypothesis (Ha) and the rejection of the null hypothesis (Ho). This finding aligned with previous research that emphasized the role of structured repetition in vocabulary learning. The drilling technique effectively strengthened vocabulary retention and allowed students to apply new words in vocabulary mastery.